Plasma digoxin levels in infants. Issue 1 (January 1973) - O'Malley, K.; Coleman, E. N.; Doig, W. B.; Stevenson, I. H.
Abstract : The average dosage rate of digoxin given in a group of infants, when related to body surface area, was twice as high (and when related to body weight, five times as high) as that employed for the maintenance therapy of adult controls. The resulting plasma digoxin level in infants older than 1 month was no higher on average than that of the adult controls (1·4 ng/ml); in those younger than 1 month it was on average 2 times higher than the adults' control value yet without toxic effect. From the preliminary findings the plasma digoxin level appears to be of limited value in regulating digoxin dosage in infancy.